Two stage integrated class-F RF power amplifier - A'ain, Abu Khari; Huang, Min Zee; Kordesch, Albert Victor (Institute of Electrical and Electronics Engineering (IEEE), 2007)
A new design of an integrated two-stage class-F power amplifier (PA) for wireless application operating in the 1.65 GHz frequency range is described. The circuit utilizes a simple method to drive the output stage with a half sinusoidal waveform that is optimal for class-F operation. The circuit was fabricated in a Silterra's standard 0.18 mum RF CMOS technology. Measurement result shows a maximum power-added efficiency (PAE) of 42% and a maximum gain of 19.7 dB. When operating from a 3 V voltage supply, the PA delivers an output power of 18.9 dBm. This work demonstrates the feasibility of using class-F PAs for short-range and low-power applications.